1990
DOI: 10.1007/bf02126293
|View full text |Cite
|
Sign up to set email alerts
|

Six-year follow up of phenylalanine intakes and plasma phenylalanine concentrations

Abstract: The daily Phe intakes of normally growing 1- to 6-year-old treated PKU patients were evaluated. The children received protein in amounts that varied from 2.26 +/- 0.47 g/kg body weight per day (mean +/- SD) at the age of 6 to 1.81 +/- 0.35 at the age of 72 months. Mean Phe intakes declining from 34 +/- 7 at the age of 6 months to 15 +/- 5 mg/kg body weight per day at the age of 72 months were required to maintain mean median plasma Phe levels around 6.0 mg/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Patient compliance to dietary recommendations tends to decrease after early childhood ). Wendel et al (1990) reported a steady decrease in frequency of blood Phe level monitoring after 6 months of age. In addition to reduced blood Phe monitoring, there is a continual increase in Phe concentrations as patients age.…”
Section: Dietary Therapymentioning
confidence: 93%
See 3 more Smart Citations
“…Patient compliance to dietary recommendations tends to decrease after early childhood ). Wendel et al (1990) reported a steady decrease in frequency of blood Phe level monitoring after 6 months of age. In addition to reduced blood Phe monitoring, there is a continual increase in Phe concentrations as patients age.…”
Section: Dietary Therapymentioning
confidence: 93%
“…The participants' protein intake per kg body weight decreased by approximately 20 percent whereas Phe intake dropped approximately 56 percent (Wendel et al 1990). …”
Section: Dietary Therapymentioning
confidence: 95%
See 2 more Smart Citations
“…Plasma phenylalanine and methionine were analyzed by ion exchange chromatography with an LKB Biochrom 20 analyser (Pharmacia Biotech, Cambridge, England). The index of dietary control (IDC) was calculated as the average of the medians of plasma phenylalanine concentrations (Wendel et al, 1990) obtained every 6 months of metabolic monitoring of patients (phenylalanine was measured every 15 days on dried blood spot samples). All samples were obtained after a 10-h overnight fast.…”
Section: Methodsmentioning
confidence: 99%